Orbital myositis associated with celiac disease - ÇERMAN, EREN; ERASLAN, MUHSİN (SPRINGER, 2014)
A 26-year-old female patient presented with redness, lid edema on the right eye and diplopia on left gaze. There was a minimal limitation of adduction of the right eye, accompanied with pain and diplopia. Orbital magnetic resonance imaging confirmed the diagnosis of orbital myositis. Anti-endomysial immunoglobulin (Ig) A, anti-endomysial IgG, anti-gliadin IgA and anti-tissue transglutaminase IgG antibodies were positive, while other tests for autoimmune diseases were unremarkable. The patient stated that her diarrhea had been relieved by a gluten-free diet. Methylprednisolone therapy (1 mg/kg) was started and on her next visit her complaints were relieved. Later, methotrexate (15 mg/week) was added to the therapy as the patient became steroid-dependent, and she has been attack-free for the last 3 months under methotrexate and low-dose methylprednisolone (4 mg/day) treatment. Associations between orbital myositis and various autoimmune diseases have previously been reported. We report here the first case of associated orbital myositis and celiac disease.
Keywords: Orbital myositis; Celiac disease; Methotrexate; GLUTEN-FREE DIET